Secured e-payment system based on automated authentication data and iterated salted hash algorithm - Ali Al Farawn; Hasanein D. Rjeib; Nabeel Salih Ali; Basheer Al-Sadawi (Universitas Ahmad Dahlan, 2020)
Electronic payment has been considered as one of the most significant and convenient applications of modern electronic services e-University compared to traditional methods that impose time-consuming, human resources, and inefficiency. Different automatic identification technologies have been widely used, such as radio frequency identification (RFID). Extensive research and several applications are focusing on taking the maximum advantage of RFID technology. Data and information security had considered a crucial role when information concerning e-commerce, e-banking, or e-payments, especially due to it required real data to establish accessed illegally. Hence, data originality and security fall a very significant and critical issue in data communication services in recent years. Applications such as e-banking or e-commerce regularly contain sensitive and personal information that should be managed and controlled by authorized persons. Thus, keeping a secure password is important to prevent unauthorized users from illegal access. The password hashing is one of the safety methods and means of preventing attacks. In this article, focuses on proposing an RFID based electronic payment and also provide multi-level security privileges for an academic domain by using RFID technology besides the programmable logic circuit as well the system used VB.Net C# environment also desktop and web-based application for system working purposes. The proposed system aims to manage student payments in a secure manner and provides the capabilities of getting a bus ticket, copying books, buying food, paying registration fees, and other services. The results have shown the system is secured by using the confirmation code in addition to password encryption.